Dismantling the Barriers to Entry. - HARRIS, RICH (Communications of the ACM, 2015)
The article discusses the state of web page development for interactive web sites. The author argues that there is a transition from web sites that were developed by front end developers to sites that are designed with more modern programming architecture. Topics discussed include the evolution of web developer programming tools, such as Ractive.js, discussion forums such as Ember core, and training of web programmers. The article also presents illustrated examples of what the author describes as best practices.